Pungitius pungitius pungitius (Linnaeus 1758 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Pungitius pungitius (Linnaeus, 1758). Ninespine Stickleback. To 9 cm (3.5 in) TL. Circumboreal; Korea to Seas of Japan and Okhotsk to Bering, Chukchi, and Beaufort Seas, and western and northern Gulf of Alaska coasts into northeastern British Columbia. Anadromous and resident freshwater forms; marine populations most common in marshes and estuaries; depth: very shallow waters to 110 m (361 ft). All in Mecklenburg et al. (2002), Page and Burr (1991), and Coad (1995). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 102, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...